2004
DOI: 10.1114/b:abme.0000036643.45452.6d
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Steady and Pulsating Velocity Profiles and Shear Rates in Arteries Using Echo PIV: In Vitro Validation Studies

Abstract: Although accurate measurement of velocity profiles, multiple velocity vectors, and shear stress in arteries is important, there is still no easy method to obtain such information in vivo. We report on the utility of combining ultrasound contrast imaging with particle image velocimetry (PIV) for noninvasive measurement of velocity vectors. This method (echo PIV) takes advantage of the strong backscatter characteristics of small gas-filled microbubbles (contrast) seeded into the flow. The method was tested in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…However, we have shown experimentally 25,26 and other investigators have shown clinically 27 by echocardiographic particle imaging velocimetry 28 that transmitral flow can produce an intraventricular rotational body of fluid referred to as a vortex ring. [29][30][31] A vortex ring has been shown to support more efficient fluid transport compared with a straight jet alone 32,33 ; thus, formation of a vortex alongside a diastolic filling jet suggests efficient transmitral blood transport.…”
mentioning
confidence: 62%
“…However, we have shown experimentally 25,26 and other investigators have shown clinically 27 by echocardiographic particle imaging velocimetry 28 that transmitral flow can produce an intraventricular rotational body of fluid referred to as a vortex ring. [29][30][31] A vortex ring has been shown to support more efficient fluid transport compared with a straight jet alone 32,33 ; thus, formation of a vortex alongside a diastolic filling jet suggests efficient transmitral blood transport.…”
mentioning
confidence: 62%
“…To induce a large amount of scattering, high concentrations of scattering particles are applied. However, due to the requirement of very high particle concentrations (Kim et al 2004a), the application of USV for in vivo applications is limited. Additionally, the presence of velocity gradients seriously affects the USV performance (Adrian 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the method produces instantaneous, two-dimensional velocity vector fields. UIV has been used to study flow in straight [23,24] and curved tubes [25], vessel phantoms [26] and vortex phantoms [27], and for preliminary in vivo investigations in healthy arteries [26,28 -30] and the heart [28,31].…”
Section: Introductionmentioning
confidence: 99%